2023
DOI: 10.1097/bs9.0000000000000158
|View full text |Cite
|
Sign up to set email alerts
|

Role of the bone marrow vascular niche in chemotherapy for MLL-AF9-induced acute myeloid leukemia

Abstract: Leukemia stem cells in acute myeloid leukemia (AML) can persist within unique bone marrow niches similar to those of healthy hematopoietic stem cells and resist chemotherapy. In the context of AML, endothelial cells (ECs) are crucial components of these niches that appear to promote malignant expansion despite treatment. To better understand these interactions, we developed a real-time cell cycle-tracking mouse model of AML (Fucci-MA9) with an aim of unraveling why quiescent leukemia cells are more resistant t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…Most importantly, these EC-fused AML cells retain the ability to trigger a full-blown relapse upon transplantation, illustrating their potential to act as a hidden reservoir of residual disease. Interestingly, Xu et al [189] have recently shown in an MLL-AF9 AML mouse model that nearly half of AML blasts in resting phase were observed within 0 to 4 µm from blood vessels, suggesting that quiescent leukaemic cells make cell-cell contact with ECs to evade therapy. Indeed, several mRNAs associated with the development of leukaemia, including Dusp6, Klf4, and Plxnb2, were significantly elevated in ECs and resting leukaemia cells after chemotherapy.…”
Section: Endothelial Cells and Progenitorsmentioning
confidence: 99%
“…Most importantly, these EC-fused AML cells retain the ability to trigger a full-blown relapse upon transplantation, illustrating their potential to act as a hidden reservoir of residual disease. Interestingly, Xu et al [189] have recently shown in an MLL-AF9 AML mouse model that nearly half of AML blasts in resting phase were observed within 0 to 4 µm from blood vessels, suggesting that quiescent leukaemic cells make cell-cell contact with ECs to evade therapy. Indeed, several mRNAs associated with the development of leukaemia, including Dusp6, Klf4, and Plxnb2, were significantly elevated in ECs and resting leukaemia cells after chemotherapy.…”
Section: Endothelial Cells and Progenitorsmentioning
confidence: 99%